THINKING MAPS - AN EFFECTIVE VISUAL STRATEGY EFL/ESL FOR LEARNERS IN 21ST CENTURY LEARNING - Islami Hakim, Muhammad Lintang (LET: Linguistics, Literature and English Teaching Journal, 2018)
In this 21st Century learning students are encouraged to master skills that can enhance their professional in their lives. The traditional method to teach English now is suggested to be integrated with the standard modern method to Enhance higher order thinking skill. Thinking Maps is a language of eight visual patterns, each based on a fundamental thought process, designed by Dr. David N. Hyerle. Looking at to the demands in teaching English, educators need to consider Thinking Maps to their English instruction. The goals of this strategy are to help teacher having a variety of technique in teaching English and to cover the demand of 21st century learning in Enhance students? thinking skill. Aware towards a potential of this teaching strategy, Thinking Maps could be one consideration for teacher to practice in the classroom. This paper will elaborate on how the Thinking maps implement can give the contributions in teaching and learning English. The discussion will be in the introduction of Thinking Maps, the concept of Thinking Maps in English language teaching. Furthermore, the application of Thinking Maps into real instructional context will be elaborated.